2015
DOI: 10.1007/s10384-015-0381-5
|View full text |Cite
|
Sign up to set email alerts
|

Indications for and effects of Nunchaku-style silicone tube intubation for primary acquired lacrimal drainage obstruction

Abstract: NSTI is effective for treating PALDO; however, EN-DCR is more effective for treating PALDO cases complicated by dacryocystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 21 publications
3
38
0
Order By: Relevance
“…First described by Kurihashi in 1993, the NST was developed as a new type of lacrimal stent, i.e., a push-toinsert lacrimal stent utilizing a stainless inner probe for insertion [17]. In retrospective studies, the reported success rate of SI by NST for the treatment of nasolacrimal duct obstruction ranged from 68 to 87.5 %, and from 75.9 to 94.6 % for the treatment of common canalicular obstruction [1,2,6,10]. The success rate of SI by NST in the present study was 81.2 % (69/85).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…First described by Kurihashi in 1993, the NST was developed as a new type of lacrimal stent, i.e., a push-toinsert lacrimal stent utilizing a stainless inner probe for insertion [17]. In retrospective studies, the reported success rate of SI by NST for the treatment of nasolacrimal duct obstruction ranged from 68 to 87.5 %, and from 75.9 to 94.6 % for the treatment of common canalicular obstruction [1,2,6,10]. The success rate of SI by NST in the present study was 81.2 % (69/85).…”
Section: Discussionmentioning
confidence: 98%
“…Dacryocystorhinostomy (DCR) is a primary surgical pathway for the treatment of lacrimal drainage duct obstruction. However, due to the invasiveness of the procedure, (i.e., bone resection and general anesthesia when necessary), reconstructive surgery by silicone intubation (SI) has been employed as an alternative treatment method [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies of Nunchaku-style tubes describe stent placement primarily under local anesthesia with infraorbital nerve block and topical anesthetic, with some cases requiring intravenous sedation or general anesthesia. 4,6,18 However, these studies included a variety of indications such as complete nasolacrimal duct obstruction and distal obstructions, which may affect anesthesia choice. In earlier studies of traditional bicanalicular intubation systems, general anesthesia was often used.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 In previous studies of Nunchaku-style tubes, operative times ranged from 7 to 10.5 mins when reported. 4,18 However, the indication for tube placement varied and often included distal and complete nasolacrimal duct obstruction, which may influence operative time. 4,18 Our mean operative time of 4.6 mins is comparable to these studies and was significantly shorter compared to the Ritleng system, but further investigation is needed with larger sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…[47] However, given its simple and timesaving technique and its low cost, intubation with silicone is widely used to treat patients with partial or complete nasolacrimal duct obstruction. [2,8,9] In patients with failed silicone nasolacrimal duct intubation (FNDI), DCR is often the recommended therapeutic approach.…”
Section: Introductionmentioning
confidence: 99%